Thin Metal Electrodes for Semitransparent Organic Photovoltaics - Lee, Kyu-Sung; Kim, Inho; Yeon, Chang Bong; Lim, Jung Wook; Yun, Sun Jin; Jabbour, Ghassan E. (WILEY, 2013)
We demonstrate semitransparent organic photovoltaics (OPVs) based on thin metal electrodes and polymer photoactive layers consisting of poly(3-hexylthiophene) and [6,6]-phenyl C-61 butyric acid methyl ester. The power conversion efficiency of a semitransparent OPV device comprising a 15-nm silver (Ag) rear electrode is 1.98% under AM 1.5-G illumination through the indium-tin-oxide side of the front anode at 100 mW/cm(2) with 15.6% average transmittance of the entire cell in the visible wavelength range. As its thickness increases, a thin Ag electrode mainly influences the enhancement of the short circuit current density and fill factor. Its relatively low absorption intensity makes a Ag thin film a viable option for semitransparent electrodes compatible with organic layers.
Keywords: POLYMER SOLAR-CELLS; EFFICIENT